Caracterización petrológica del Plutón de La Hoya, jurásico medio a superior del batolito patagónico en Esquel - Boltshauser, Barbara (2019)
The La Hoya Pluton is composed of two main facies, a porphyritic biotitic monzogranite that grades into a porphyritic granodiorite with hornblende and biotite, and a subordinated tonalitic to dioritic one that locally intrudes the former two. This pluton bears magma hybridization textures, such as microgranular mafic enclaves, synplutonic dikes, and ocellar quartz. An 40Ar/39Ar cooling age in amphibole of 161.49±0.46 Ma allows us to assign this pluton to the the early stages of the Patagonian Batholith. Basaltic dikes which intrude the pluton have a máximum 40Ar39Ar age obtained in plagioclase of 42.15 ± 0.40 Ma (Eocene), thus correlatable with the Pilcaniyeu Belt of the Andean Paleogene volcanism. The La Hoya Pluton is calc-alkaline, metaluminous, magnesian and Itype, with garnet-free sources. Mineral chemistry analysis conducted in plagioclases and hornblendes threw crystallization conditions between 670-930°C and 0.5-6Kb. These values are coherent with a moderately deep source and a shallow emplacement level, which is also supported by the presence of miarolitic cavities and graphic textures.